Biomimetic 3D in vitro model of biofilm triggered osteomyelitis for investigating hematopoiesis during bone marrow infections - Raic, Annamarija; Bieback, Karen (Acta biomaterialia, 2019)
In this work, we define the requirements for a human cell-based osteomyelitis model which overcomes the limitations of state of the art animal models. Osteomyelitis is a severe and difficult to treat infection of the bone that develops rapidly, making it difficult to study in humans. We have developed a 3D in vitro model of the bone marrow, comprising a macroporous material, human hematopoietic stem and progenitor cells (HSPCs) and mesenchymal stromal cells (MSCs). Inclusion of biofilms grown on an implant into the model system allowed us to study the effects of postoperative osteomyelitis-inducing bacteria on the bone marrow. The bacteria influenced the myeloid differentiation of HSPCs as well as MSC cytokine expression and the MSC ability to support HSPC maintenance. In conclusion, we provide a new 3D in vitro model which meets all the requirements for investigating the impact of osteomyelitis. - Statement of Significance - Implant-associated osteomyelitis is a persistent bacterial infection of the bone which occurs in many implant patients and can result in functional impairments or even entire loss of the extremity. Nevertheless, surprisingly little is known on the triangle interaction between implant material, bacterial biofilm and affected bone tissue. Closing this gap of knowledge would be crucial for the fundamental understanding of the disease and the development of novel treatment strategies. For this purpose, we developed the first biomaterial-based system that is able to mimic implant-associated osteomyelitis outside of the body, thus, opening the avenue to study this fatal disease in the laboratory.
Gesehen am 02.04.2019